Andean bear Tremarctos ornatus (Carnivora: Ursidae) presence in the Amazon tropical forest of Peru - Figueroa, Judith (Instituto de Ecología, A.C., 2012)
In Peru, the Andean bear (Tremarctos ornatus) inhabit primarily montain forest, between 1900 to 2350 m of altitude. In contrast, the records in the Amazon tropical forest (BTA), under 650 mof elevation, are rare. The presence of this species was evaluated in the BTA of the boundaries of the Yanachaga Chemillén National Park with the Yanesha Communal Reserve (PNYC-RCY, 32.8 km), during the months of February/2005 and July/2007, and the Amarakaeri Communal Reserve (RCA, 190.96 km) during the months of April-May and August/2008. In the first case, a relative abundance of0.081 records/km during the rainy season and 0.829 records/km during the dry season. In the second, the Andean bear was absent during the rainy season and of 0.032 records/km in the dry season. The presence in the BTA during the dry season, could be related to the consumption of palms (Arecaceae), because the fruits that are the base of its diet in the montane and premontane forest are mature in the rainy season. In addition, at PNYC-RCY, the BTA could be used as a corridor for the movement of the Andean bear to other montane areas, taking advantage of the low water level on the river due to the lack of rain.